-3(2y-6)+6+7y=4

Simple and best practice solution for -3(2y-6)+6+7y=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2y-6)+6+7y=4 equation:


Simplifying
-3(2y + -6) + 6 + 7y = 4

Reorder the terms:
-3(-6 + 2y) + 6 + 7y = 4
(-6 * -3 + 2y * -3) + 6 + 7y = 4
(18 + -6y) + 6 + 7y = 4

Reorder the terms:
18 + 6 + -6y + 7y = 4

Combine like terms: 18 + 6 = 24
24 + -6y + 7y = 4

Combine like terms: -6y + 7y = 1y
24 + 1y = 4

Solving
24 + 1y = 4

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 1y = 4 + -24

Combine like terms: 24 + -24 = 0
0 + 1y = 4 + -24
1y = 4 + -24

Combine like terms: 4 + -24 = -20
1y = -20

Divide each side by '1'.
y = -20

Simplifying
y = -20

See similar equations:

| 324000000=2.4x+180 | | 3-12b=-9 | | 2.5+1.6k+3k+4.5=2.7k-0.9k | | 0.04x+0.20(80-x)=0.15(80) | | 4+2n=4 | | 3-3.7b=10.3b+0 | | 5+3b=17 | | 2x^3-5x^2+7x=0 | | y=-10.6-8 | | 2m-3=17 | | (x-5)(x+8)=8(x-2) | | 2.5+14.1k=3.6k | | 3-3.7b=10.3b | | 98x^3/y^5 | | 17x-20-7x=2(6x-4) | | 265-x=200 | | 1-3m=-17 | | 5q+4=8q-5 | | 4k^2+8k=0 | | -8d-5d+7d=71 | | 18+b=x | | 5x21/2 | | -r-4=-2 | | 2a-(5/a-1)=0 | | 99n+4=40 | | 5x-13=38 | | 3u-3=3u-6 | | 0=p+19 | | x-35=0 | | F(k+2)=3(2)+7 | | 21/26y=7 | | 23=23+x |

Equations solver categories